ANALISIS SISTEM DAN PROSEDUR TERHADAP PENERIMAAN DAN PENGELUARAN KAS HOTEL SAHID MONTANA DUA MALANG - Fajriani Listya Awal (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to analyze the implementation of systems and procedures for cash receipts and disbursements.The method used is a descriptive method with a qualitative approach. The techniques used are interview, observation and documentation and literature reviews relating to the cash receipts and disbursements of the hotel. The results show that the some aspects of system and procedures on the cash receipts and disbursements of Sahid Montana Dua Hotel Malang have been conducted based on standard operational procedures and worked effectively and efficiently. For example, job rotation and employee turnover activities have been conducted using best practices which the qualities have been matched with responsibilities and all forms is pre-numbered. However, there are still some double positions and no flowchart made, hence the hotel cannot view directly the deficiencies of systems and procedures. Moreover, a sudden inspection by the leadership Hotel Sahid Montana Dua Malang is not conducted yet.Keywords : Systems, Procedures, Cash Receipts, Cash Disbursements